If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -12 = 2x + 6 Reorder the terms: -12 + x = 2x + 6 Reorder the terms: -12 + x = 6 + 2x Solving -12 + x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + x + -2x = 6 + 2x + -2x Combine like terms: x + -2x = -1x -12 + -1x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + -1x = 6 + 0 -12 + -1x = 6 Add '12' to each side of the equation. -12 + 12 + -1x = 6 + 12 Combine like terms: -12 + 12 = 0 0 + -1x = 6 + 12 -1x = 6 + 12 Combine like terms: 6 + 12 = 18 -1x = 18 Divide each side by '-1'. x = -18 Simplifying x = -18
| 10-3=57 | | 8x-13=59 | | 2=8-x | | y/(-6.5)=-6 | | 5x+15=12x-6 | | 5h+211-h=-5 | | 2(x+4)=2x+15-7 | | 2w^2-3w-20=0 | | f(5)=(3)(5)-2 | | 6+7(-3z+4)=-9(4z-7)+6 | | -7(2-4x)=-14 | | 4x-7y-2y+9x+11= | | 6e^3x=39 | | -5(x+1)=-6-5x | | -(4y+5)-(-3y-8)=2 | | 2d+10=6d-19 | | c-7=3 | | m/(-10)=55 | | 12n=-6n-24n | | f(2)=(3)(2)-2 | | 3eightsp=9 | | -1(5x+5)=0 | | c+7=3 | | 4u-32=-4u | | 4n=356 | | 6(x+4)=11x+5 | | 10x=6y+2 | | -67=-7(-7+x)+5(-4x-7) | | f(-2)=(3)(-2)-2 | | -14.5+1.5y=-31 | | 1.2x^2+2.5x=1.8 | | 90+18x=108 |